Banking on 'break-out': finance and the development of ethnic minority businesses. - Ram, Monder; Smallbone, David; Deakins, David; Jones, Trevor (Journal of Ethnic & Migration Studies, 2003)
Reflecting recent changes in the pattern of ethnic minority business activity in Britain, this paper examines the experiences of firms attempting to break out from the cramped range of generally marginal activities historically occupied by South Asian, African-Caribbean and other immigrant-origin entrepreneurs. Based on in-depth case histories supplemented by a large-scale quantitative survey, the present paper addresses the financial experiences of these firms in the light of the assumption that break-out entails a shift from labour-intensive to capital-intensive activities requiring external financing. Access to bank credit continues to be problematic, with frequent perceptions of racist discrimination even in the case of entrepreneurs with seemingly impressive track records and personal resource endowments.